Capacity Analysis of Two-lane Highways Operating under Non-ideal Conditions (2015)
The highway system is an important component of the transportation system in many countries of the world. Studies have shown that many factors contribute to capacity reduction of highways. Traffic steam characteristics of three highways in Ibadan metropolis were captured in 2011. Models were developed to quantify the prevailing conditions of the roads. The capacity analysis of the roads was carried out based on the methodologies described in the United States Highway Capacity Manual (HCM 2000).The traffic stream was heterogeneous in nature. The analysis showed that the highways were operating under non-ideal conditions which resulted in capacity reduction and performance level. The resulting models are useful in evaluating capacity performance of two-lane highways for Improved optimization of the system